The History and Exegetical Thought of Bahrul Anam’s Tafsir al-Qur’an al-‘Azim - Syafe’i; Komaruddin Sassi (CV. Creative Tugu Pena, 2025)
Qur’anic exegesis is a vital instrument for understanding divine messages in a profound and applicable manner. One distinctive contribution to the landscape of contemporary Indonesian tafsir is Tafsir al-Qur’an al-‘Azim authored by KH. Bahrul Anam. This study aims to explore the historical background of its writing, the methodological approaches employed, and the exegetical characteristics that define Bahrul Anam’s work, particularly in bridging classical Islamic scholarship with the needs of contemporary Muslim society. Using a qualitative library-research approach, this study closely examines the content of the tafsir alongside relevant supporting works, including references from both classical and modern scholars. The findings indicate that Tafsir al-Qur’an al-‘Azim adopts a thematic–contextual approach while remaining firmly grounded in both tafsir bi al-ma’tsur and tafsir bi al-ra’yi. Bahrul Anam presents his interpretations in an accessible and down-to-earth language, making them easily understood by general readers. The work highlights social issues such as justice, humanity, family, education, religious moderation, and nationalism. Consequently, this tafsir serves not only as an interpretation of the sacred text but also as an instrument of moral, social, and national transformation that remains highly relevant amid the evolving dynamics of Indonesian Muslim society.